A numerical experiment on the influence of the interannual variation of sea surface temperature on terrestrial precipitation in northern Japan during the cold season. Issue 11 (26th November 2013) - Sato, Tomonori; Sugimoto, Shiori
<x xml:space="preserve">Abstract</x> [1] The role of sea surface temperature (SST) anomaly in modulating the terrestrial precipitation in winter around Japan was investigated using a regional atmospheric model. Large amount of snowfall occurs as the westerly winter monsoon carries abundant moisture from the Japan Sea. An experiment with realistic SST gives improved representation of terrestrial precipitation distribution compared to the reanalysis. The standard deviation of interannual variation of precipitation in the experiment was approximately 20% larger over the Kuroshio extension than that in the experiment with climatology SST, suggesting that the SST variability enhances the oceanic precipitation variability. For the role of Japan Sea, the terrestrial precipitation over the Japan Sea side (JSS) region in northern Japan was sensitive to the offshore SST anomaly through affecting moisture flux toward Japan. Since the offshore SST was clearly warmer in the 2000s relative to the 1980s, the effect of the long‐term SST variation on the terrestrial precipitation trend was examined. The experiment with realistic SST simulated the observed trend in terrestrial precipitation in the JSS region. In contrast, the precipitation trend was significantly reduced in the experiment with climatology SST. Therefore, the long‐term SST trend is an important factor for the precipitation trend in the region of Japan and the adjacent oceans where SST has significant trends. Precipitation in southern Japan facing the Pacific Ocean indicated increasing trend even without the SST trend. This suggests that the long‐term variations in extratropical cyclones are also an important factor for precipitation trends around the Kuroshio extension.